A Case of Midgut Volvulus Associated with a Jejunal Diverticulum. (19th December 2017) - Gutowski, Joseph; NeMoyer, Rachel; Parker, Glenn S.
Abstract : Midgut volvulus in adults is a rare entity that may present with intermittent colicky abdominal pain mixed with completely asymptomatic episodes. This small bowel twist may result in complications of obstruction, ischemia, hemorrhage, or perforation. With a midgut volvulus, complications may be life-threatening, and emergent surgical intervention is the mainstay of treatment. This current case involves an 80-year-old woman with intermittent abdominal pain with increasing severity and decreasing interval of time to presentation. A CAT scan revealed mesenteric swirling with possible internal hernia. A diagnostic laparoscopy followed by laparotomy revealed a midgut volvulus, extensive adhesions involving the root of the mesentery, and a large jejunal diverticulum. The adhesions were lysed enabling untwisting of the bowel, allowing placement of the small bowel in the correct anatomic position and resection of the jejunal diverticulum. This is a rare case of midgut volvulus with intermittent abdominal pain, associated with jejunal diverticulum managed successfully. A midgut volvulus should be considered in the differential diagnosis of a patient who present with a small bowel obstruction secondary to an internal hernia, especially when a swirl sign is present on the CAT scan.